Novel Targets for Drug Use in Eosinophilic Granulomatosis With Polyangiitis - Uzzo, Martina; Regola, Francesca; Trezzi, Barbara; Toniati, Paola; Franceschini, Franco; Sinico, Renato Alberto (Frontiers in Medicine, 2021)
Eosinophilic Granulomatosis with Polyangiitis (EGPA) is a rare autoimmune disease characterised by medium and small vessels inflammation. Cardiac vasculitic involvement is one of the most severe manifestations with a significant impact on patients’ long-term prognosis: anyway, a specific therapeutic approach for heart involvement in EGPA has not been explored yet. Current regimen consists of a long-term therapy with high dose of glucocorticoids, causing the well-known related-adverse events; immunosuppressive drugs are used in patients with severe manifestations, with some limitations. New therapeutic approaches are needed for patients with refractory disease or contraindications to conventional therapies. The quest for the ideal therapy is going towards a more and more personalized approach: on the one hand, efforts are made to use already existing therapies in the most appropriate way; on the other hand, new insights into EGPA pathogenesis allow the discovery of new targets, as demonstrated by mepolizumab and rituximab, targeting eosinophils and B-cell compartments. This review summarizes the emerging therapies used in EGPA, focusing on the most recent studies on biologics and analyzing their efficacy and safety.